A Maturity Framework for Zero-Trust Security in Multiaccess Edge Computing. (29th June 2022) - Ali, Belal; Hijjawi, Simsam; Campbell, Leith H.; Gregory, Mark A.; Li, Shuo
Abstract : Multiaccess Edge Computing (MEC) has been adopted to provide an environment that supports cloud computing capabilities and IT services at the network edge. The open architecture of cloud computing and network access at the edge provides malicious actors with many attack vectors. The MEC system entities cannot be permanently trusted due to the dynamic and shareable nature of MEC deployments. This paper presents a classification of MEC entities that can be used to define security controls based on the Zero-Trust Security approach. The security controls are organised into a maturity framework that can be used to guide the systematic development of trust and security in an MEC environment. In this framework, a Minimum Viable Security posture defines the first operational step towards full implementation of Zero-Trust Security in an MEC environment.